Pengaruh Profitabilitas, Likuiditas, Leverage, dan Ukuran Perusahaan Terhadap Kebijakan Dividen Saham-saham yang Terdaftar pada Jakarta Islamic Index (JII) Periode Tahun 2011-2015 - Parmitasari, Rika Dwi Ayu; Hasrianto, Hasrianto (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2017)
Dividend policy becomes an important financial policy, not only from the company management side, but also from shareholders. Shareholders will apply for dividends if the company makes a profit. The growth of the Jakarta Islamic Index industry which tends to be good and stable earnings will be easier and focused to see profitability, liquidity, leverage, and firm size affect dividend payout ratio and of course dividend payout ratio. Based on the statement can be seen that investors want a stable dividend policy. However, in fact, the average growth of dividend payout ratio during the period 2010-2015 fluctuated and did not indicate the implementation of a stable dividend policy. This study aims to obtain empirical evidence about the influence of profitability, liquidity, leverage, and size of the company against dividend policy. The approach taken in this research is quantitative approach. Sample selection method in this study is purposive sampling is the method of selecting the sample by using some certain criteria so that get 11 samples of companies listed in the Jakarta Islamic Index period of 2011-2015, which amounted to 30 companies. The analysis method used is financial analysis, classical assumption test, multiple regression analysis, coefficient of determination, F test and t test. The results of this study indicate that the variables of profitability, liquidity, leverage and firm size affect simultaneously to dividend policy. Partial test shows that the variable profitability, liquidity, and size of the company have a positive and significant impact on dividend policy. Meanwhile, leverage has a negative and insignificant effect on dividend policy. The coefficient of determination showed 59.9%. These results indicate the ability of independent variables in explaining the dependent variable while 40.1% is explained by other variables. The results of this study can provide information or as a signal to the public and outside parties or investors to take investment decisions and assess the financial performance of a company.